Beneficial synergy of adsorption–intercalation–conversion mechanisms in Nb2O5@nitrogen-doped carbon frameworks for promoted removal of metal ions via hybrid capacitive deionization. Issue 1 (18th December 2020) - Wang, Guizhi; Yan, Tingting; Shen, Junjie; Zhang, Jianping; Shi, Liyi; Zhang, Dengsong
Abstract : Enhanced removal of metal ions in a hybrid capacitive deionization system has been originally developed via the adsorption–intercalation–conversion mechanisms. Abstract : Capacitive deionization (CDI) is an emerging water purification technology, but the ion adsorption capacity of traditional carbon-based CDI electrodes is still unsatisfactory. Herein, a novel faradaic electrode by anchoring Nb2 O5 nanoparticles on nitrogen-doped carbon frameworks as anodes and activated carbon (AC) as cathodes in a hybrid capacitive deionization (HCDI) system was originally developed to capture Na + ions via adsorption–intercalation–conversion mechanisms. The synergistic effects of the nanostructure and carbon coating were beneficial to enhancing electrical conductivity and offering fast Na + ion diffusion pathways. Impressively, the HCDI system demonstrated an excellent ion adsorption capacity of 35.4 mg g −1 in a 500 mg L −1 NaCl solution at 1.2 V as well as stable regeneration ability. In situ Raman and ex situ XPS measurements unraveled that the mechanism of ion removal from water was the reversible redox reaction of Nb2 O5 . The new overall understanding of the synergistic effects opens opportunities for the design of HCDI systems for efficient removal of metal ions from saline water.